UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BIJI JAMBU BOL (Syzygium malaccense L) TERHADAP BAKTERI Bacillus subtilis : UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL BIJI JAMBU BOL (Syzygium malaccense L) TERHADAP BAKTERI Bacillus subtilis - Rosa Devitria; Yowantyano Dwiki Riaunanda (LPPM Universitas Abdurrab, 2025)
Abstract Infectious diseases are medical disorders caused by pathogenic bacteria that infect and multiply within the body in large numbers, leading to illness. Antibiotics are the choice for combating infections and diseases caused by pathogenic bacteria. Guava seeds can be used as a natural ingredient for medicinal plants because they contain secondary metabolite compounds such as flavonoids, phenols, and terpenoids, which are known to have activities as antioxidants, antibacterial, antifungal, antiviral, and anticancer agents. The purpose of this study is to determine the antibacterial activity of ethanol extract of guava seeds in inhibiting the growth of Bacillus subtilis bacteria. The method used in this study is the Kirby-Bauer method, which is a disk diffusion method. Based on the results of the research conducted with concentrations of 20%, 40%, 60%, and 80%, with varying results of 12.43 mm, 15.37 mm, 15.78 mm, and 16.67 mm. These results can be concluded that the inhibition zone produced by the guava seed extract against Bacillus subtilis bacteria falls into the category of strong inhibitory